LITERATUR REVIEW: Analisis Peran Guru Sebagai Motivator dalam Meningkatkan Motivasi - Sulfina Sufya Sufya; Wihdatul Af'al; Adel Mursi Sofiana Safitri; Wilda (Universitas Muhammadiyah Kolaka Utara, 2025)
Teachers play an important role as motivators in enhancing students’ learning motivation.Learning motivation influences students’ activeness, interest, and achievement of learningoutcomes, and is related to academic, social, and emotional aspects. This study aims to examinethe role of teachers in increasing learning motivation through various methods, media, strategies,and learning approaches. The research method employs a literature review with a descriptiveapproach, analyzing 10 articles from national journals indexed in Google Scholar and SINTA.The results indicate that teachers can enhance learning motivation through strategies such asproviding reinforcement and rewards, implementing varied learning methods, utilizing engagingmedia, creating a conducive learning environment, and giving constructive feedback. Thisincrease in motivation is reflected in higher scores, percentages, and students’ averageachievement. The study emphasizes the importance of teacher innovation in learning methods andstrategies that align with students’ characteristics, and serves as a reference for teachers andresearchers in developing more effective learning strategies in the future